Karakteristik Dan Pola Konsumsi Zat Gizi Pasien Penyakit Jantung Koroner Rawat Jalan Di RSUD Kota Mataram - Ninik Sari; Suhaema Suhaema; Aladhiana Cahyaningrum; Abdul Salam (Poltekkes Kemenkes Mataram, 2018)
Background. Coronary Heart Disease is a disease caused by narrowing of the arteries due to atherosclerosis or koroneria spasm or both. Result Health Research (RISKESDAS) in 2013 showed the prevalence of coronary heart disease nation wide reached 1,5%. Nusa Tenggara Barat (NTB) province is one of the province where the prevalence of coronary heart disease is higher than the national prevalence rate, which at 2,1%.Research Methods. This is an observasional study. Population, all outpatients in hospitals Kota Mataram experiencing coronary heart diseasesince the month of January-October 2015 as many as 83 people. Sampel, number of samples is 40, data collected in the form of data sample characteristics include age, gender, level of education, nutritional status, long-suffering CHD, LDL levels and data consumption fats, carbohydrates, fiber, vitamin A, vitamin C and Vitamin E samples.Research Result. The results showed the level of fat consumption the most categories in the above categories, namely the needsof 21 people ( 52,5%). Highest level of carbohydrate consumption that the deficit category as many as 36 people ( 90,0%). The level of fiber consumption at no more than the deficit category as many as 34 people (85,0%). The level of consumption of vitamin A in the category of needs as many as 40 people (100,0%). The level of consumption of vitamin C category deficits as many as 25 people (62,5%). The level of consumption of vitamin E most of the above categories, namely needs 19 people (47,5%)Conclusion. The consumption level entry, vitamin E and vitamin A in the category above needs, while the level of consumption of carbohydrates, fiber and vitamin C samples are in the deficit category